Delay analysis of ultra high speed InAlAs/InGaAs high electron mobility transistor. (2014) - Mohapatra, Meryleen; Shukla, Nutan; Panda, A.K.
This work deals with the DC, RF and delay analysis of a InAlAs/InGaAs based high electron mobility transistor with different gate lengths viz. 50 nm, 35 nm and 15 nm. A maximum drain current (Idss ) of 398 mA/mm is achieved at Vds of 0.4 V for a 15 nm gate length device which is more as compared to 50 nm and 35 nm gate length HEMT with a current of 368 mA/mm, 384 mA/mm respectively. A cutoff frequency (fT ) of 1.3 THz is obtained for a 15 nm gate length HEMT while a cutoff frequency of 625 GHz and 1.05 THz has been achieved for a 50 nm and 35 nm gate length devices. A maximum oscillation frequency (fmax ) of 1.8 THz has been reported for a 15 nm gate length device where as a fmax of 1.35 THz and 1.58 THz has been obtained for a 50 nm and 35 nm gate length HEMT. For a 50 nm, 35 nm and 15 nm gate length HEMT the transit time obtained is 0.42 psec, 0.3 psec, 0.22 psec respectively.